THE ROLE OF SELECTING AND SYSTEMATIZATION OF EDUCATIONAL MATERIALS IN ENHANCING LINGUACULTURAL COMPETENCE IN STUDENTS (TAMADDUN NURI JURNALI, 2024)
Linguacultural competence integrates linguistic ability and cultural understanding, essential for effective communication in diverse settings. This study investigates the selection and systematization of educational materials aimed at enhancing linguacultural competence in students. Criteria for evaluating materials and a framework for their organization are proposed, based on a comprehensive literature review and empirical analysis. Findings highlight the importance of culturally relevant and pedagogically sound resources, offering practical recommendations for educators and curriculum developers.